1993
DOI: 10.1007/bf00133016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEG and other additives on cyclodextrin production by Bacillus macerans cyclomaltodextrin-glycosyl-transferase

Abstract: The effect of PEG and other polyols additives on cyclodextrins (CDs) production by Bacillus mucerans cyclomaltodextrin-glycosyl-transferase (CGTase) was investigated. Mannitol, glycerol and PEG-200 (2O%.v/v) enhanced the enzymatic production yield regardless of substrate concentration. Furthermore, the PEG-200 addition increased the thermostability of the CGTase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Finally, we checked the stability of different CGTase preparations in the presence of ethanol, a cosolvent proposed by some authors for the improvement of the CGTase in the production of cyclodextrins (Delbourg et al, 1993; Shiraishi et al, 1989; Abraham, 1995; Mori et al, 1995). Figure 4 shows that the glyoxyl‐agarose immobilized enzyme was much more stable than any other preparation under these conditions (by more than a 100‐fold factor).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we checked the stability of different CGTase preparations in the presence of ethanol, a cosolvent proposed by some authors for the improvement of the CGTase in the production of cyclodextrins (Delbourg et al, 1993; Shiraishi et al, 1989; Abraham, 1995; Mori et al, 1995). Figure 4 shows that the glyoxyl‐agarose immobilized enzyme was much more stable than any other preparation under these conditions (by more than a 100‐fold factor).…”
Section: Resultsmentioning
confidence: 99%
“…Different organic compounds have been used in many instances to improve the CD yields or to alter the percentage of the CD produced. Several authors have intended to explain this effect (Delbourg et al, 1993; Shiraishi et al, 1989; Abraham, 1995; Mori et al, 1995). Taking advantage of the high stability of the CGTase‐glyoxyl‐agarose preparation in the presence of ethanol even at a concentration of 30%, it was possible to compare the effect of the ethanol in the reaction rate of production of β‐CD from starch or maltodextrins with the β‐CD degradation with maltose as acceptor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies revealed that the addition of PEG leads to an increase in the thermal stability of some enzymes (31)(32)(33). Therefore, the effect of PEG 2000 on the thermal sensitivity of Fuc-TVII was examined by preincubating at different temperatures for 1 h with or without PEG 2000, followed by measurement of its residual activity at 37°C.…”
Section: Preparation Of Fuc-tvii-mentioning
confidence: 99%